PK-modifying anchors significantly alter clearance kinetics, tissue distribution, and efficacy of therapeutics siRNAs - Bruno M.D.C. Godinho; Emily G. Knox; Samuel Hildebrand; James W. Gilbert; Dimas Echeverria; Zachary Kennedy; Reka A. Haraszti; Chantal M. Ferguson; Andrew H. Coles; Annabelle Biscans; Jillian Caiazzi; Julia F. Alterman; et al. (Elsevier, 2022)
Effective systemic delivery of small interfering RNAs (siRNAs) to tissues other than liver remains a challenge. siRNAs are small (∼15 kDa) and therefore rapidly cleared by the kidneys, resulting in limited blood residence times and tissue exposure. Current strategies to improve the unfavorable pharmacokinetic (PK) properties of siRNAs rely on enhancing binding to serum proteins through extensive phosphorothioate modifications or by conjugation of targeting ligands. Here, we describe an alternative strategy for enhancing blood and tissue PK based on dynamic modulation of the overall size of the siRNA. We engineered a high-affinity universal oligonucleotide anchor conjugated to a high-molecular-weight moiety, which binds to the 3' end of the guide strand of an asymmetric siRNA. Data showed a strong correlation between the size of the PK-modifying anchor and clearance kinetics. Large 40-kDa PK-modifying anchors reduced renal clearance by ∼23-fold and improved tissue exposure area under the curve (AUC) by ∼26-fold, resulting in increased extrahepatic tissue retention (∼3- to 5-fold). Furthermore, PK-modifying oligonucleotide anchors allowed for straightforward and versatile modulation of blood residence times and biodistribution of a panel of chemically distinct ligands. The effects were more pronounced for conjugates with low lipophilicity (e.g., N-Acetylgalactosamine [GalNAc]), where significant improvement in uptake by hepatocytes and dose-dependent silencing in the liver was observed.